(untitled) (Fiep Bulletin - online, 2014)
It is noticed that a larger amount of the society is looking for the practice of physical activities, because these aid in the preservation and promotion of the health, once epidemic studies come demonstrated expressive association between an active lifestyle and a smaller death possibility. The risks for the health, particularly the cardiovascular ones, current of the moderate physical exercise are low and they can still become more reduced through the evaluation pré-participation that allows practice guided by the professional of Physical Education. Of the risks, the largest is the sudden death related to the physical activity, that usually feels 30 seconds after the pick of the physical activity that caused this fact, and 90% of the victims of sudden death had a heart disease not diagnosed, so in most of the cases this event can be forewarned. The objective of this article is to state clearly how many academies in Curitiba, registered in 2005 on Cref-Pr, request medical examination before the beginning of the sport practice in their facilities, tends like this a parameter to classify the safety and prevention of the same ones regarding sudden death. Besides it is intended to know which exams are requested in those academies, relating like this with the medical literature, that it proposes a complete medical evaluation, composed of a construction of medical report (anamnesis) and exams as the Electrocardiogram, ecocardiograma and effort test.